Accuracy of Bleeding Volume as a Predictor of Mortality in Epidural Hemorrhage Patients Undergoing Surgery at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Stefiyan, Ferdi; Trijoso Permono; Erial Bahar (Sriwijaya Journal of Surgery, 2023)
Introduction: EDH is a collection of blood clots between the dura layer and the cranium. This is usually caused by rupture of the middle meningeal artery but can also be caused by rupture of the dural venous sinus, diploic vein, meningeal vein, or bleeding from the fracture line. CT scan is the investigation of choice to detect intracranial injury after trauma. CT scans can also identify additional features that influence the results, namely, midline shifting, blood clot thickness and hematoma volume, cerebral edema, and cranium fractures. This study aimed to determine the accuracy of bleeding volume as a predictor of mortality in epidural hemorrhage patients undergoing surgery at Dr. Mohammad Hoesin General Hospital, Palembang Indonesia. Methods: This study is a retrospective study of prognostic tests to determine the accuracy of bleeding volume as a predictor of mortality in patients with EDH who underwent surgery at Dr. Mohammad Hoesin General Hospital. This study uses secondary data obtained from medical record data at the medical records installation of Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. A total of 106 research subjects participated in this study. Results: The sensitivity value of bleeding volume was 77.7%, and specificity was 78.3%, and also obtained a positive predictive value of 7.21% and a negative predictive value of 97.4%, it can be concluded that bleeding volume is not accurate as a predictor of mortality. Conclusion: Bleeding volume is not an accurate predictor of mortality in epidural hemorrhage patients undergoing surgery at Dr. Mohammad Hoesin General Hospital, Palembang Indonesia.